2019
DOI: 10.1021/jacs.9b09359
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Divergent Total Synthesis of (−)-Epicoccin G and (−)-Rostratin A Enabled by Double C(sp3)–H Activation

Abstract: Dithiodiketopiperazines are complex polycyclic natural products possessing a variety of interesting biological activities. Despite their interest, relatively few total syntheses have been completed. We herein report the enantioselective, scalable, and divergent total synthesis of two symmetrical pentacyclic dithiodiketopiperazines, (−)-epicoccin G and (−)-rostratin A. A common intermediate was synthesized on a multigram scale from inexpensive, commercially available starting materials using an enantioselective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 42 publications
1
23
0
3
Order By: Relevance
“…Indeed, DFT calculations indicated that the cis,cis 6-5-6-5-6 pentacyclic system is more stable than the trans,trans system by 5kcal mol À1 . [17] To the best of our knowledge,n o total synthesis of a trans-fused pentacyclic DTP naturalp roduct was reported prior to this study,t hus underlining the difficulty to access these particulars tructures. The presence of four contiguous stereocenters makes this target even more arduous to synthesize.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, DFT calculations indicated that the cis,cis 6-5-6-5-6 pentacyclic system is more stable than the trans,trans system by 5kcal mol À1 . [17] To the best of our knowledge,n o total synthesis of a trans-fused pentacyclic DTP naturalp roduct was reported prior to this study,t hus underlining the difficulty to access these particulars tructures. The presence of four contiguous stereocenters makes this target even more arduous to synthesize.…”
Section: Introductionmentioning
confidence: 90%
“…[16] In this article, we report in detail our investigations that led to the concise,s calable and divergent enantioselective total synthesis of two complex DTP natural products,( À)-epiccocin G( 1)a nd (À)-rostratin A( 2), which were synthesized for the second and first time, respectively. [17] This achievementw as enabled by an ew strategy based on an efficient double Pd 0 -catalyzed C(sp 3 )ÀHa ctivation reaction as ak ey step. Structurally, these two naturalp roducts display distinctive oxidative degree at C5/C5', different sulfurated functionalities at C2/C2', and the presence of cis (1)o rtrans (2)A -B/D-E ring junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Thepower of this ring-forming multiple CÀHf unctionalization strategy was recently demonstrated in amore complex setting.Itwas indeed akey strategy in the divergent synthesis of the fused pentacyclic dithiodiketopiperazines (DTPs) (À)epicoccin G( 42)a nd (À)-rostratin A( 43), bioactive secondary metabolites of fungal origin, [49] which was reported by our group in 2019 (Scheme 9). [50] These targets were obtained in 7a nd 11 steps,r espectively,f rom the less functionalized common intermediate 44,w hich is here the CÀHf unctionalization retron. In particular,t he two alkenes in 44 were employed to access both cis and trans A-B/D-E ring junctions found in the natural products.T he trans-fused system is particularly challenging to install and DTPs such as 43 had so far resisted total synthesis.R etron 44 was constructed from ditriflate 45 through Pd 0 -catalyzed double C(sp 3 )ÀHa lkeny-…”
Section: Late-stage Functionalization Of A(poly)cyclic Frameworkmentioning
confidence: 99%
“…Es war die Schlüsselstrategie in der divergenten Synthese der fusionierten pent-azyklischen Dithiodiketopiperazine (DTP) (À)-Epicoccin G (42)u nd (À)-Rostratin A( 43), bioaktive Sekundärmetaboliten pilzlichen Ursprungs, [49] welche von unserer Gruppe in 2019 berichtet wurde. [50] Diese Zielmoleküle wurden in 7bzw. 11 Schritten von dem weniger funktionalisierten gemeinsamen Zwischenprodukt 44 erhalten, welches in diesem Fall das C-H-Funktionalisierungs-Retron ist.…”
Section: Kurzaufsätzeunclassified
“…[54] Die in diesem Fall verwendete Pyridingruppe kann, verglichen zu anderen zweizähnigen dirigierenden Gruppen, unter milden Reaktionsbedingungen entfernt werden und verhindert somit die Epimerisierung des etwas empfindlichen Stereozentrums.D ie Amide 60 a-c wurden durch Palladium(II)-katalysierte C(sp 3 )-H-Arylierung mit den passenden Aryliodiden synthetisiert [22] und die entsprechenden Amidvorläufer wurden von Methyl-d-lactat erhalten. Diese Methode erlaubte die divergierende Einführung verschiedener Arylgruppen, einschließlich solcher mit Chlor-o der Bromsubstituenten, die in den Aeruginosinen 98A und 98C enthalten sind (50)(51). Insgesamt veranschaulicht die Synthese der Aeruginosine das Interesse an katalytischen C-H-Funktionalisierungen,s owohl fürk onvergente (einfache Synthese von mehreren Fragmenten aus dem chiralen Pool) als auch divergente (einfacher Zugang zu analo-gen Fragmenten und durch die Erweiterung auf mehrere Kongenere) Vorgehensweisen.…”
Section: Kurzaufsätzeunclassified